Stability considerations for drug-device combination products-21 CFR part 4 update - Christopher Latoz; Laure Larkin; Kim Huynh-Ba (SpringerOpen, 2023)
Abstract Combination products are therapeutic and diagnostic products that include two or more of the following: drug, biologic, and device. These products are needed for enhanced clinical outcomes and have more than one Mode of Action (MOA). Therefore, they require a more complex regulatory pathway and compliance with a minimum of two (2) sets of regulatory standards. In 2013, the 21 Code of Federal Regulations (CFR) Part 4 was published to clarify the applicable GMP regulations when drugs, devices, or biological products are included. The FDA (U.S. Food and Drug Administration) released additional guidance in 2017 to streamline the regulatory framework and provide transparency about demonstrating GMP compliance when multiple regulatory standards overlap. This paper summarizes the Current Good Manufacturing Practice (CGMP) requirements for drug-device combination products (Biologic combinations are not discussed in this paper). Emphasis is placed on considerations for structuring a compliant drug-device stability program, including the use of bracketing and matrixing the test schedule to support the establishment of the product expiry date and how legacy products can be evaluated to meet current standards.